2‐Arylpropylamines from 1‐Propenylbenzenes in a New One‐Pot Metathesis–Hydroaminomethylation Protocol. Issue 3 (18th January 2023) - Avendaño‐Villarreal, Jesus A.; Delolo, Fábio G.; Granato, Artur V.; Gusevskaya, Elena V.; dos Santos, Eduardo N.
Abstract: 2‐Arylpropylamines are useful as active pharmaceutical ingredients (APIs) and as synthetic building blocks in fine chemistry. Herein we report a new and efficient methodology to transform naturally occurring 1‐propenylbenzenes into 2‐arylpropylamines employing a one‐pot ethenolysis/hydroaminomethylation protocol. Four consecutive reactions must occur in the same reaction vessel and the careful selection of the reaction conditions was critical to obtain the desired products in high yields. The negative interference between the ethenolysis and the hydroaminomethylation (HAM) catalysts was circumvented by the appropriate adjustment on the molar ratio of the catalysts. As a result, nine 2‐arylpropylamines were obtained in yields ranging in 75–93 %. Abstract : A new one‐pot protocol involving ruthenium‐catalyzed ethenolysis and rhodium‐catalyzed hydroaminomethylation was developed employing commercially available pre‐catalysts. Nine 2‐arylpropylamines were synthesized from naturally occurring 1‐propenylbenzenes employing this straightforward methodology in good yields.